Evaluation of the dosimetric accuracy of the AAA algorithm (Analytical Anisotropic Algorithm) of the eclipse treatment planning system (2016)
Abstract. This current work evaluates the dosimetric accuracy of version 11.0.31 of the AAA algorithm for calculating the photon dose distributions of the Eclipse treatment planning system respect to the input data. The accuracy of the algorithm was analized for the two photon energy spectrums available on the linear accelerator Clinac iX: 6 MeV and 15 MeV, was calculated. To perform the evaluation of the AAA algorithm was calculated the percentage differences between its values calculated with the respective measured values taking into account the tolerances and recommendations described in the Task Group report 53. Relative dosimetry was evaluated carefully and it could be observed that a decreasing of this agreement as the depth of the measurement increased, as well as the increase in field size. In the evaluation of the relative dosimetries for both photon energy spectrums, it was found that overall results of percentage agreement was in the inner zone 92.3 % of the points passed the tests, while for the penumbra zone, umbra and build-up the percentage of points which passed the test were 92.4 %, 14.8 % and 100 % respectively. Absolute dosimetry was analyzed in a homogeneous phantom simulator and additionally, we constructed and characterized imageologically a thorax phantom to analyze the accuracy of the algorithm under conditions of inhomogeneity of the medium.